Minat Generasi Milenial terhadap Pekerjaan di Bidang Pertanian di Kabupaten Sukoharjo (Dipayungi oleh Program Merdeka Belajar Kampus Merdeka Pembelajaran Studi Agroteknologi 4) - Ningrum, Melinawati Dwi Cahya; Setyowati, Retno; Widiyanti, Emi (Universitas Muhammadiyah Semarang, 2023)
Most of the population of Sukoharjo Regency have a livelihood as farmers and farm laborers. At this time, almost all the farmers and farm laborers are old farmers. This is due to the phenomenon of aging farmers and reduced youth workforce and the low interest of the millennial generation in work in agriculture. This study aims to find out how the millennial generation is interested in jobs in agriculture and to find out the factors that influence the interest of the millennial generation. The research method used is qualitatively descriptive. The results showed that the millennial generation's interest in working in agriculture in Kartasura District and Bendosari District, Sukoharjo Regency was seen from perception, involvement, attention, and motivation. There are two factors that influence the interest of the millennial generation, namely driving factors and inhibiting factors. The driving factors include inheritance of agricultural land, introduction of agriculture by parents, sharing of knowledge about agriculture by parents, supporting natural resources, encouragement from the government, and being able to open jobs in agriculture. Inhibiting factors include limited agricultural land, non-agricultural work, low social status, no interest in agriculture, no formal education in agriculture, and lack of family income in agriculture.